«Сергей Иваныч»: Об одном «герое» мандельштамовского «Шума времени» [“Sergei Ivanych”: A Note on Mandel’shtam’s “The Noise of Time”] - Mets, Alexander (Slavica Revalensia, 2017)
“Sergei Ivanych” is a chapter from Osip Mandel’shtam’s autobiographical narrative The Noise of Time (1925). The article represents some newly discovered details of the life story of Mandel’shtam’s private teacher Sergei Ivanovich Belyavsky(1883—1953).